2008
DOI: 10.1038/npp.2008.202
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Depletion Impairs Waiting but not Stop-Signal Reaction Time in Rats: Implications for Theories of the Role of 5-HT in Behavioral Inhibition

Abstract: Central serotonin (5-HT) function is thought to be a critical component of behavioral inhibition and impulse control. However, in recent clinical studies, 5-HT manipulations failed to affect stop-signal reaction time (SSRT), which is a fundamental process in behavioral inhibition. We investigated the effect of central 5-HT depletion (intracerebroventricular 5,7-dihydroxytryptamine) in rats on two aspects of behavioral inhibition, SSRT and 'waiting', using the stop-signal task. 5-HT depletion had no effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 69 publications
6
87
0
Order By: Relevance
“…Recent studies have focused on mechanisms of behavioral inhibition and pinpointed the integration of a network including the orbitofrontal cortex, the dorsomedial striatum, and the subthalamic nucleus, that normally inhibits many forms of behavior, including both impulsivity and compulsivity (for a review, see ref. 29). Our behavioral data suggest that overexpression of CK1δ in the forebrain might disturb this network balance and produce some form of impulsivity.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have focused on mechanisms of behavioral inhibition and pinpointed the integration of a network including the orbitofrontal cortex, the dorsomedial striatum, and the subthalamic nucleus, that normally inhibits many forms of behavior, including both impulsivity and compulsivity (for a review, see ref. 29). Our behavioral data suggest that overexpression of CK1δ in the forebrain might disturb this network balance and produce some form of impulsivity.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, TD was found to affect Go/NoGo responding to a greater extent in males with a history of alcoholism (LeMarquand et al, 1999) or in healthy volunteers where responding was suppressed by punishment (Crockett et al, 2009). By contrast, TD had no effect on stop-signal reaction-time performance in healthy subjects Cools et al, 2005) in parallel with a similar lack of effect of serotonin depletion in rats (Eagle et al, 2009).…”
Section: Serotonin Depletion Promotes Impulsive Actionmentioning
confidence: 88%
“…Thus, studies in rats and humans have shown that manipulating 5-HT does not affect performance on tasks of inhibition that have no clear affective component, such as the stop-signal reaction-time task Cools et al, 2005;Chamberlain et al, 2006;Bari et al, 2009;Eagle et al, 2009), the self-ordered spatial working memory task (Walker et al, 2009), and the go-nogo task (Rubia et al, 2005;Evers et al, 2006) (but see LeMarquand et al, 1999).…”
Section: The Coupling Between Inhibitory and Aversive Effects Of Seromentioning
confidence: 99%